Effect of four irrigation doses and four varieties on agronomical characteristics and yield of cotton cultivation in central Greece: Cotton irrigation yield - Darawsheh, Mohammed K.; Kakabouki, Ioanna; Folina, Antigolena; Karydogianni, Stella; Katsenios, Nikolaos; Zisi, Charikleia (Journal of Aridland Agriculture, 2020)
In recent years, reduced irrigation has been applied for the cultivation of cotton. While this strategy remains desirable, it needs to be evaluated as it affects the yields and growth of cotton. During 2015 and 2016, two similar cotton experiments (Gossypium hirsutum L.) were performed in Greece, in the area of Karditsa and especially in the location of Palamas. An experiment was established designed according to split-plot design, with main plots four levels of irrigation (IRR. 2, IRR. 4, IRR. 6, IRR. 8) and subplots four varieties of cotton (Dp 419, Campo, Andromeda, Lider) for two growing periods. The results indicated that agronomical characteristics were affected by irrigation dose, while LAI (Leaf Area Index) was affected by irrigation levels and year. LAI higher values were noticed in RR8 level for all varieties. Second year values of LAI were higher than the first year. Irrigation levels affected the number of closed bolls. Closed bolls were ranged from 12 (RR2 with variety Dp 419) to 144.67 (RR8 in same variety). The yield was significantly affected by irrigation levels and variety; the highest value was observed in second year by the Lider variety (3,110 kg ha-1). A strong positive correlation was mentioned between yield and total fresh weight (r=0.72, p=0.001). On a pooled basis, all varieties responded positively to the largest amount of irrigation (RR8).